Calcium Homeostasis and Bone Metabolism in Goats Fed a Low Protein Diet - Mi, Hui; Li, Haobang; Jiang, Weimin; Song, Wu; Yan, Qiongxian; He, Zhixiong; Tan, Zhiliang (Frontiers in Veterinary Science, 2022)
The objective of this study was to investigate the effects of low-protein diets on blood calcium (Ca) level, bone metabolism, and the correlation between bone metabolism and blood calcium in goats. Twenty-four female Xiangdong black goats with similar body weight (19.55 ± 3.55 kg) and age (8.0 ± 0.3 months) were selected and allocated into two groups: control group (CON, 10.77% protein content) and low-protein group (LP, 5.52% protein content). Blood samples were collected on days 1, 4, 7, 16 and 36 before morning feeding to determine the concentration of calcium (Ca), parathyroid hormone (PTH), bone gla protein (BGP), C-terminal telopeptide of type 1 collagen (CTX-1), bone alkaline phosphatase (BALP), and 1, 25-dihydroxyvitamin D3 [1,25(OH)2D3]. Liver samples were collected to determine the expression of bone metabolism-related genes. There was no difference observed between LP and CON in concentration of plasma Ca or any of bone metabolism markers (P > 0.05). In the liver, the mRNA expression of bone gamma carboxyglutamate protein (BGLAP), alkaline phosphatase (ALPL), and mothers against decapentaplegic homolog-1 (SMAD1) were increased (P < 0.05) in LP as compared with CON. The correlation analysis of Ca and bone metabolism markers showed no significant correlation between Ca and bone metabolism. These results suggest that the blood Ca concentration in mature goats may keep at a stable level through nitrogen cycling when the providing protein is not enough.